1999
DOI: 10.1046/j.1420-9101.1999.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite local maladaptation in the Canarian lizard Gallotia galloti (Reptilia: Lacertidae) parasitized by haemogregarian blood parasite

Abstract: Biologists commonly assume that parasites are locally adapted since they have shorter generation times and higher fecundity than their hosts, and therefore evolve faster in the arms race against the host's defences. As a result, parasites should be better able to infect hosts within their local population than hosts from other allopatric populations. However, recent mathematical modelling has demonstrated that when hosts have higher migration rates than parasites, hosts may diversify their genes faster than pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 25 publications
4
56
0
Order By: Relevance
“…Conversely, Prugnolle et al (2006) found no evidence for S. mansoni LA to the snail (Biomphalaria glabrata) in a population where S. mansoni and B. glabrata were found to have similar migration rates. Diplostomum pseudopathaceum trematodes demonstrated local maladaptation to their more mobile fish hosts (Gasterosteus aculeatus) and a haemogregarine parasite (phylum Sporozoa) showed local maladaptation to populations of its most mobile host, the lizard Gallotia galloti (Oppliger et al, 1999). These three studies support hypothesis (3).…”
Section: Patterns Of Local Adaptation In Clpssupporting
confidence: 68%
“…Conversely, Prugnolle et al (2006) found no evidence for S. mansoni LA to the snail (Biomphalaria glabrata) in a population where S. mansoni and B. glabrata were found to have similar migration rates. Diplostomum pseudopathaceum trematodes demonstrated local maladaptation to their more mobile fish hosts (Gasterosteus aculeatus) and a haemogregarine parasite (phylum Sporozoa) showed local maladaptation to populations of its most mobile host, the lizard Gallotia galloti (Oppliger et al, 1999). These three studies support hypothesis (3).…”
Section: Patterns Of Local Adaptation In Clpssupporting
confidence: 68%
“…In the following sections we expand on the potential explanations for local Gyrodactylus maladaptation, as well as the relative importance of ecological history and evolutionary lineage as drivers of host-parasite co-evolution. Although parasites are generally expected to have an evolutionary advantage over hosts (Ebert, 1994;Saarinen and Taskinen, 2005) due to their short generation time and potentially high host specificity, parasites have not always shown signatures of local adaptation to their sympatric hosts (Kaltz et al, 1999;Oppliger et al, 1999;Koskela et al, 2000;Lemoine et al, 2012;Roth et al, 2012;Konijnendijk et al, 2013;Sternberg et al, 2013). Our study reduced the methodological limitations of many previous studies, and our data indicate that Gyrodactylus does not generally show strong local adaptation to their sympatric guppy hosts.…”
Section: Tablementioning
confidence: 51%
“…Local maladaptation has been defined both verbally and mathematically, and has been subject to extensive empirical and theoretical investigation (Gandon et al, 1996;Lively and Jokela, 1996;Morand et al, 1996;Kaltz and Shykoff, 1998;Kaltz et al, 1999;Oppliger et al, 1999;Gandon and Michalakis, 2002;Thrall et al, 2002;Dybdahl and Storfer, 2003;Kawecki and Ebert, 2004;Lively et al, 2004;Nuismer, 2006). Local adaptation has been characterized theoretically within two broad frameworks whose appropriateness is under debate: home versus away and local versus foreign (Kawecki and Ebert, 2004).…”
Section: Trait Mismatchesmentioning
confidence: 99%
“…These de-0 1991 1992 1993 1994 1995 1996 1997 1998 1999 Testing the geographic mosaic theory R Gomulkiewicz et al signs involve measuring and comparing the fitness of individuals within their natal and non-natal environments. Several studies have used such an approach to document local maladaptation in at least one member of an interacting species pair (e.g., Morand et al, 1996;Kaltz and Shykoff, 1998;Kaltz et al, 1999;Oppliger et al, 1999).…”
Section: Trait Mismatchesmentioning
confidence: 99%